IVENTARISASI SPESIES IKAN YANG BERPOTENSI DIJADIKAN IKAN HIAS DI RAWA BIRU TAMAN NASIONAL WASUR KABUPATEN MERAUKE - Norce Mote; Dwi Nugroho Wibowo (Universitas Musamus, Merauke, Papua, 2016)
Rawa Biru located in the National Park Wasur Merauke has the potential of fish resources were quite large, both for consumption and ornamental fish. The research purpose is to identify the types of fish that have the potential as ornamental fish. The study was conducted in August 2016. The method used was survey and the data was analyzed descriptively through pictures. The results were obtained six types of fish that have the potential as ornamental fish, they are Iriatherina wirneri, Melanotaenia splendida rubrostriata, Ambassis agrammus, Craterocephalus randi, Glossamia aprion, and Toxotes chatareus.